2020
DOI: 10.3390/cancers12102728
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Accelerates the Progression of Colitis-Associated Colorectal Cancer by Promoting EMT

Abstract: Recently, it has been reported that Fusobacterium nucleatum, a major pathogen involved in chronic periodontitis, may play an important role in colorectal cancer (CRC) progression. In addition, inflammatory bowel diseases such as ulcerative colitis and Crohn’s disease represent major predisposing conditions for the development of CRC, and this subtype of cancer is called colitis-associated cancer (CAC). Although the importance of F. nucleatum in CRC has attracted attention, its exact role and related mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 38 publications
(38 reference statements)
2
37
0
Order By: Relevance
“…Although F. nucleatum is associated with EMT in cancer development 19 , the involvement of p-EMT in F. nucleatum infection remains unclear. Therefore, we examined the involvement of F. nucleatum in the regulation of p-EMT of OSCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although F. nucleatum is associated with EMT in cancer development 19 , the involvement of p-EMT in F. nucleatum infection remains unclear. Therefore, we examined the involvement of F. nucleatum in the regulation of p-EMT of OSCC.…”
Section: Resultsmentioning
confidence: 99%
“…It recently has been reported that F. nucleatum is associated with EMT in cancer development. F. nucleatum decrease the levels of epithelial marker including E-cadherin and increase the levels of EMT-associated transcription factors including Snail and Slug in colorectal cancer progression 19 . Moreover, ZEB1 level is upregulated by F. nucleatum exposure in oral cancer cells 20 .…”
mentioning
confidence: 95%
“…In sporadic CRC, Fusobacterium nucleatum, through the expression of virulence factors that confer the capacity to adhere to epithelial cells and to induce the activation of the beta-Catenin and Wnt pathways, has been shown to promote cancer development (extensively reviewed in Brennan and Garrett 2019 [106] ). Recently, F. nucleatum has also been shown to worsen tumor induction in the AOM/DSS model of CAC by activating EGFR signaling pathways and promoting epithelial-to-mesenchymal transition, a key event in colon carcinogenesis [107] . The enterotoxigen Bacteroides fragilis has been shown to induce colitis and to pro-mote tumorigenesis in APC min/ + mice.…”
Section: Role Of Intestinal Microbiota In Cacmentioning
confidence: 99%
“…et al suggested that F. nucleatum well promotes epithelial to mesenchymal transition during colon cancer progression [ 24 ]. Using the cancer cell line and the AOM-DSS model of colitis-associated colon cancer, this group demonstrated that when used with epithelial barrier disruptive agent DSS, F. nucleatum synergistically increased the aggressiveness and EMT characteristics of cancer cells and this process involved EGFR signaling pathways [ 24 ]. Finally, the impact of the microbiome on the human epigenome was recently nicely overviewed by Dr. J. Allet and Dr. C. Sears [ 25 ].…”
Section: Mechanistic Links Between Microbiota and Colon Cancermentioning
confidence: 99%